2022
DOI: 10.3390/ph15050599
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Aloe Compounds in Combatting Viral Diseases

Abstract: Plants contain underutilized resources of compounds that can be employed to combat viral diseases. Aloe vera (L.) Burm. f. (syn. Aloe barbadensis Mill.) has a long history of use in traditional medicine, and A. vera extracts have been reported to possess a huge breadth of pharmacological activities. Here, we discuss the potential of A. vera compounds as antivirals and immunomodulators for the treatment of viral diseases. In particular, we highlight the use of aloe emodin and acemannan as lead compounds that sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The results showed that aloe vera gel provided better results than CHX [ 80 ]. These studies have highlighted the mechanisms of action of aloe vera which has the following: Anti-inflammatory properties thanks to the content of acemannans and anthraquinones which can reduce inflammation by acting on inflammatory processes at a cellular level [ 103 ]; Antioxidant properties thanks to the presence of vitamins C and E and flavonoids which protect cells from damage caused by free radicals [ 51 , 104 ]; Antimicrobial action preventing infections and helping to maintain oral hygiene [ 80 , 105 ]; Effects on bacterial plaque, influencing its growth and formation [ 106 ]; Effects on the immune system by helping to regulate the immune response and reduce inflammation [ 107 ]; Positive effects on wound healing by stimulating collagen production especially in the presence of small wounds or irritations caused by orthodontic devices [ 108 , 109 ]; Hydrating and soothing effects on skin and oral mucous membranes, improving patient comfort and reducing irritation [ 110 , 111 ]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that aloe vera gel provided better results than CHX [ 80 ]. These studies have highlighted the mechanisms of action of aloe vera which has the following: Anti-inflammatory properties thanks to the content of acemannans and anthraquinones which can reduce inflammation by acting on inflammatory processes at a cellular level [ 103 ]; Antioxidant properties thanks to the presence of vitamins C and E and flavonoids which protect cells from damage caused by free radicals [ 51 , 104 ]; Antimicrobial action preventing infections and helping to maintain oral hygiene [ 80 , 105 ]; Effects on bacterial plaque, influencing its growth and formation [ 106 ]; Effects on the immune system by helping to regulate the immune response and reduce inflammation [ 107 ]; Positive effects on wound healing by stimulating collagen production especially in the presence of small wounds or irritations caused by orthodontic devices [ 108 , 109 ]; Hydrating and soothing effects on skin and oral mucous membranes, improving patient comfort and reducing irritation [ 110 , 111 ]. …”
Section: Discussionmentioning
confidence: 99%
“…Hydrating and soothing effects on skin and oral mucous membranes, improving patient comfort and reducing irritation [ 110 , 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aloe compounds have the potential to be used as antiviral drugs and immunomodulators to treat viral diseases, especially the use of emodin and AC in aloe as lead compounds [ 71 ]. Infection with human immunodeficiency virus (HIV) may cause organ failure and tumor development throughout the body, which is a serious threat to life and health.…”
Section: Biological Functions Of Acmentioning
confidence: 99%
“…A neutraceutical combination of AV, Poria cocos, and rosemary extract triggered the activation markers on various types of innate immune cells, resulting in enhanced immune surveillance and antioxidant defense [ 14 ]. In C57BL/6 mice, processed AV gel given orally functions as an adjuvant for influenza vaccinations [ 15 17 ]. Alprogen and Aloe polysaccharides play a role in modulating the immune system and specifically have antiallergic effects [ 18 ].…”
Section: Introductionmentioning
confidence: 99%